TWO TOPICAL CALCINEURIN INHIBITORS FOR THE TREATMENT OF ATOPIC DERMATITIS IN PEDIATRIC PATIENTS: A META-ANALYSIS OF RANDOMIZED CLINICAL TRIALS (VARIANT OF THE ARTICLE IN RUSSIAN) - S.L. Chen; J. Yan; F.S. Wang (Union of pediatricians of Russia, 2011)
Two new topical immunomodulators, pimecrolimus cream and tacrolimus ointment for atopic dermatitis (AD) in pediatric patients, have provided alternatives to topical corticosteroids without the associated adverse events. Objective: To evaluate the efficacy and safety of tacrolimus ointment and pimecrolimus cream for the treatment of AD in pediatric patients. MEDLINE, Embase, the CNKI and Cochrane Library databases were searched up to December 2008. Additional data sources were manual searches of abstract proceedings and personal contact with investigators and pharmaceutical companies. Two investigators assessed the quality of trials with unified tables independently. Disagreements on validity assessment were resolved through discussion or consultation with the third author. Quality analysis of methodology was evaluated according to the Jadad scale, including randomization, blinding and patients' discontinuation. Twenty trials involving 6288 infants and children with AD met the inclusion criteria. More patients using tacrolimus had a good response than those in control groups including vehicle, 1% hydrocortisone acetate and 1% pimecrolimus, the corresponding OR were (4.56; 95%CI: 2.80 to 7.44), (3.92; 95% CI: 2.96 to 5.20) and (1.58; 95% CI: 1.18 to 2.12). The effect difference between 0.03% tacrolimus and 0.1% tacrolimus ointments was not statistically significant (OR = 0.90; 95% CI: 0.55 to 1.48). The incidence of adverse events of tacrolimus ointment or pimecrolimus cream was similar to the vehicle. The major adverse events were burning and pruritus. Both tacrolimus ointment and pimecrolimus cream are safe and effective in the treatment of AD in pediatric patients. Tacrolimus ointments were superior to pimecrolimus cream.Key words: atopic dermatitis, children, meta-analysis, pimecrolimus, tacrolimus.